Drug Therapy Management of Cardiovascular Disease patients admitted to intensive Care units of Tertiary care Hospitals - Ashokbhai, Prajapati Aarohi; Shrikalp, Deshpande (Indian Journal of Pharmacy Practice)
Background: Therapy in Intensive Care Unit (ICU) often involves poly pharmacy and patients require close therapy monitoring. When individualization of therapy is warranted, the role of pharmacist can prove to be the best in achieving the therapeutic goals and improve the treatment outcomes of the patients. Method: A prospective, observational study was carried out in the medical ICU of a tertiary care hospital for a period of three months. Results: A total of 100 cardiovascular disease patient files were selected and data collected was analysed for the drug therapy management. Medication prescribed was analysed using advance medication review. The mean (SD) age was found to be 58.4 (10.4) years. 65% were male and 35% were female patients with a mean (SD) of 13.49 (5.62) medicines administered per patient. A total of 174 drug related problems were identified during the study period, which were classified into drug interactions 86% (p-value 0.953), untreated indications 23% (p-value 0.727), adverse drug reactions 22%, improper drug selection 18% (p-value 0.431), therapeutic duplication 15% (p-value 0.431), patient in need of TDM 6% and drug without indication 4% (p-value 0.917). Among 100 patients 77% patients received correct therapy. Conclusion: The study showed that medication management of critically ill patients can decrease drug related problems in complex therapy as well improve the therapeutic outcome of the treatment.
Keywords: Cardiovascular diseases; Drug Therapy Management; Drug related problems; Intensive care unit; Hospital Stay; Pharmacist Remarks